Coordinated regulation of gene expression by the cell cycle transcription factor Swi4 and the protein kinase C MAP kinase pathway for yeast cell integrity. - Igual, J C (1996)
Specific transcription in late G1, mediated by the transcription factors SBF (Swi4p-Swi6p) and MBF (Mbp1p-Swi6p), is crucial for cell cycle progression in budding yeast. In order to better understand the G1/S transition, we initiated a search for conditional mutations synthetic lethal with swi4delta. One of the isolated mutants, rsf8swi4delta, showed a growth defect due to cell lysis. rsf8 is allelic to PKC1, encoding a protein kinase C homologue which controls cell integrity. In the presence of the rsf8/(pkc1-8) mutation, a functional SBF but not MBF is required for viability. Importantly, swi4delta and swi6delta strains are hypersensitive to calcofluor white and SDS, indicating that they possess a weakened cell wall. Overexpression or ectopic expression of CLN did not suppress the pkc1-8swi4delta mutant phenotype, thus SBF must control cell integrity independently, rather than acting through CLN expression. We found that at least six genes involved in cell wall biosynthesis are periodically expressed at the G1/S phase boundary. In all six cases, cell cycle-regulated expression is due mainly to Swi4p. Finally, we found that the PKC1 MAP kinase pathway is a positive regulator of five of these cell wall genes, these genes being novel targets of regulation by this pathway. We suggest that SBF and the PKC1 MAP kinase pathway act in concert to maintain cell integrity during bud formation.